Molecular Detection and Characterization of Pasteurella multocida Infecting Camels in Marsabit and Turkana Counties, Kenya - Justus K. Kasivalu; George I. Omwenga; Gabriel O. Aboge (International Journal of Microbiology)
Pasteurella multocida infection is common in Kenya though there is little knowledge of the genetic diversity of the pathogen. P. multocida is part of the normal flora in the respiratory tract of camels, but it becomes pathogenic when the resistance of the camel body is diminished by bad ecological conditions. This study was conducted to detect, characterize, and determine the genetic diversity of P. multocida infecting camels in Marsabit and Turkana Counties. The KMT1 gene was targeted as the marker gene for P. multocida and hyaD-hyaC, bcbD, dcbF, ecbJ, and fcbD as marker genes for capsular serogroups A, B, D, E, and F, respectively. Out of 102 blood and 30 nasal swab samples, twenty-one samples (16%) were confirmed to be positive for P. multocida and only capsular group E was detected in both counties. The P. multocida sequences were highly conserved and were related to strains from other parts of the world. Our study has confirmed that camels in Marsabit and Turkana Counties of Kenya are infected by P. multocida of capsular type E. Farmers should not underfeed camels, ensure appropriate medication and vaccination programs, and minimize herding of camels in crowded areas especially in wet conditions in order to slow the spread of P. multocida infection.